THE EFFECTIVENESS OF SPATIAL DATA SHARING IN INDONESIA-SDI: CASE STUDY IN MINISTRY OF ENVIRONMENT AND FORESTRY AND PROVINCIAL GOVERNMENT OF WEST JAVA - Sahroni, Wulan Yustia (MAJALAH ILMIAH GLOBE, 2017)
ABSTRACTIt has been almost ten years since the issuance of Presidential Decree No. 85 Year 2007 on the National Spatial Data Infrastructure (NSDI) as a milestone of data sharing in Indonesia. Even since Law No. 4 of 2011 on Geospatial Information was established, the implementation of the NSDI among institutions and local governments has still not been effective yet, which can be seen from the amount of participants in Ina-Geoportal. Not all agencies and local government involved and active in the data sharing through Ina-Geoportal. The study was conducted  in order to identified the problems causing the ineffectiveness of data sharing and give the recommendations as solutions, taking the case in the Ministry of Environment and Forestry and the Provincial Government of West Java. The problems will be analyzed from the component of policy, institutional, technology, standard, and human resources. Method conducted are in a form of interviews, questionnaire, content analysis, and statistical descriptive to determine the rank of each component in each agency. The result showed that the effectiveness of data sharing in three agencies are 67,36% with institutional as the most ineffective and technology as a good and supportive component. Provide a road-map for the clarity of the work in each agency, applying metadata standard and feature catalogue of Indonesia, complements a topographic map as a reference map, and a strong commitment from all parties involved are the recommendations given so that the process of data sharing runs effectively in support of national development planning.Keywords: spatial data sharing, NSDI, policy, regulation, content analysis, descriptive statisticABSTRAKSudah hampir sepuluh tahun sejak diterbitkannya Peraturan Presiden Nomor 85 Tahun 2007 tentang Infrastruktur Data Spasial Nasional (IDSN) sebagai tonggak berjalannya data sharing di Indonesia. Bahkan sejak Undang-undang Nomor 4 tahun 2011 tentang Informasi Geospasial diresmikan sebagai payung hukum yang lebih kuat, pelaksanaan NSDI antar instansi dan daerah belum berjalan dengan efektif, terlihat dari jumlah partisipan dalam Ina-Geoportal sebagai infrastruktur berbagi pakai. Belum seluruh instansi dan pemerintah daerah terlibat dalam Ina-Geoportal. Penelitian ini ditulis untuk mengidentifikasi permasalahan penyebab belum efektifnya berbagi-pakai data di Kementerian Lingkungan Hidup dan Kehutanan dan Pemerintah Provinsi Jawa Barat, serta memberikan rekomendasi sebagai solusi dalam komponen kebijakan, pengaturan kelembagaan, teknologi, standar, dan sumber daya manusia. Metode deksriptif kuantitatif dalam bentuk interview, kuesioner, analisis konten, dan deskriptif statistik dilakukan untuk mengetahui peringkat setiap komponen dalam pelaksanaan berbagi pakai di tiap instansi. Hasil analisa menunjukkan tingkat efektivitas berbagi pakai di tiga instansi tersebut sebesar 67,36% dimana pengaturan kelembagaan menjadi komponen yang dianggap paling tidak menunjang dan teknologi menjadi komponen yang paling baik dari sudut pandang pengguna. Rekomendasi diberikan sebagai solusi untuk setiap permasalahan dalam tiap komponen, diantaranya perlu adanya road-map untuk kejelasan pekerjaan, menerapkan standar metadata dan katalog unsur geografi indonesia, melengkapi peta Rupabumi Indonesia sebagai acuan pemetaan, dan komitmen kuat dari seluruh pihak yang terlibat. Rekomendasi ini diberikan untuk menunjang kegiatan berbagi pakai yang efektif dalam mendukung perencanaan pembangunan nasional.Kata Kunci:    berbagi pakai data spasial, NSDI, kebijakan, peraturan, perundangan, analisa konten, statistik deskriptif